Three-dimensional indoor positioning based on IMU/magnetometer sensor fusion - Leong, Jaaron (Nanyang Technological University, 2022)
Location-based services have been gaining popularity lately with the advancement of technologies. Global positioning system is being used worldwide, but is met with accuracy errors in indoor environments. Hence, the demand for research on different indoor positioning technologies is high. Nevertheless, indoor positioning approaches are restricted by the inertial sensors’ drift errors and the inaccuracies of the compasses. This work aims to propose an indoor positioning approach based on designed electromagnetic fields combined with Inertial Measurement Units (IMUs). The IMU sensors used are commercially available smartphones, and the established system has to be done offline without the need for external sensors and infrastructures. The proposed system results will be analysed, and practical applications will be discussed.